The challenges of undocumented migrant childhood - Albański, Łukasz (Kultura-Społeczeństwo-Edukacja, 2018)
This article examines the concept of undocumented childhood. Undocumented children have to navigate between protected (as minors) and unprotected (as young adults) contexts. Therefore, they live not only in a relatively difficult situation as children staying in another country, but also face other risks due to their uncertain futures. Their situation calls for a re-examination of the frame that has been triggered to incorporate them. In particular, one may ask: what does it mean to provide children with rights and protections that ultimately expire. Thus, the article aims to bring the discussion about children as a minority group back. It helps to assure that migrant children will be considered as children first, and not as foreigners.